Centrosema pubescens Benth growth under nitrogen and sulfur fertilization more sulfur in Ecuador - López-Hidalgo, Hilda Beatriz (Universidad Autónoma de Tamaulipas, 2017)
The quality and availability of forage, mainly from grasses, decreases in the tropical regions during the dry season, since when it matures it increases the content of structural carbohydrates and decreases the protein and the digestibility. The objective of this study was to evaluate the initial growth of Centrosema pubescens Benth, under nitrogen and sulfur fertilization. The planting of C. pubescens was carried out in black polyethylene  bags. Two treatments of nitrogen fertilization 0 kg/Nha-1 (-NS) and 44 kg/Nha-1 (+NS) were evaluated using ammonium sulfate as the nitrogen source. Fertilization was done at the time of planting, at 15 d, 30 d and 60 d after sowing. The experiment lasted 12 weeks and weekly sampling of the following variables was done: number of nodules (NN), nodule weight (NW), root length (RL), partially dry matter (PDM), plant height (PH), leaf area index (LAI), net accumulation rate (NAR), crop growth  rate (CGR), relative growth rate (RGC) and specific leaf area (SLA). A regression analysis was used to estimate growth curves and trend lines. The +NS treatment caused a significant  decrease of NN (- 10) and NW (- 0.72 g)  (P < 0.05). Nonsignificant result was observed in RL (P > 0.05) with 42.0 cm and 42.8 cm for +NS and -NS, respectively. However, for  PDM and PH the treatments affected positivity their behavior (P < 0.05). The rest of  the variables (LAI, NAR, CGR, RGR and SLA) were not affected by the treatments (P > 0.05). Fertilization with nitrogen plus sulfur improved the establishment of C. pubescens for fodder purposes.